ANALISIS HABITAT KOLONI LEBAH HUTAN APIS DORSATA DAN KUALITAS MADU YANG DIHASILKAN DARI KAWASAN HUTAN DENGAN TUJUAN KHUSUS (KHDTK) RANTAU, KALIMANTAN SELATAN - Yelin Adalina (Pusat Penelitian dan Pengembangan Hutan, 2018)
ABSTRACTForest Area with Special Purpose (KHDTK) Rantau is a research forest (HP) in South Kalimantan where there is a beehive tree (sialang) regularly inhabited by Apis dorsata forest bee colonies. The existence of sialangtrees are sources of honey for forest honey collectors around the area. The research was conducted to determine (1) the potential of Rantau HP as sialang habitat and (2) the quality of honey produced through survey and observation approaches. Vegetation analysis was used to determine the vegetation structure of plants of bee feed sources in the beehive siege habitat. The physicochemical test of honey was used to analyze the quality of honey based on water content, pH, hydroxymethylfurfural (HMF) content, acidity level, reducing sugar content, and phytochemical content. The analysis showed that there were 17 species of tree, 7 species of poles, 7 species of saplings and 8 species of seedlings. The highest Important Value Index (IVI) at the tree level was Acacia mangium (62.0%) as the source of the nectar, at pole level was Vitex pinnata (63.2%) as the sourceof pollen, at the sapling level was Glochidion sp. (53.5%) as the source of pollen, and at level of seedlings was Ficus variegata (34.3%) as the source of pollen. The results of laboratory analysis showed that harvested foresthoney meet the Indonesian National Standard (SNI) 01-3545-2013, with the exception of the water content. Honey contains phytochemical components of flavonoids, alkaloids, saponins, and triterpenoids.Key words: Vegetation analysis, Apis dorsata, honey quality, bee foragesABSTRAKKawasan Hutan Dengan Tujuan Khusus (KHDTK) Rantau merupakan hutan penelitian (HP) di Kalimantan Selatan dimana terdapat pohon sialang yang secara regular dihuni koloni lebah hutan Apis dorsata. Keberadaan pohon sialang menjadi sumber penghasil madu bagi pemungut madu hutan di sekitar kawasan. Penelitian telah dilakukan untuk mengetahui (1) potensi HP Rantau sebagai habitat sialang dan (2) kualitas madu yang dihasilkan melalui pendekatan survei dan observasi. Analisis vegetasi digunakan untuk mengetahui struktur vegetasi tumbuhan sumber pakan di habitat kepungan sialang. Uji fisikokimia madu digunakan untuk menganalisis kualitas madu berdasarkan kadar air, pH, kandungan hidroksimetilfurfural (HMF), kadar keasaman, kandungan gula pereduksi, dan kandungan fitokimia. Hasil analisis vegetasi menunjukkan spesies sumber pakan terdapat 17 jenis untuk tingkat pohon, 7 jenis tingkat tiang, 7 jenis tingkat pancang dan 8 jenis tingkat semai. Nilai INP tertinggi tingkat pohon adalah Acacia mangium (62,0%) sebagai sumber nektar, tingkat tiang Vitex pinnata (63,2 %) sebagai sumber polen, tingkat pancang Glochidion sp. (53,5%) sebagai sumber polen, dan tingkat semai Ficus variegata (34,3%) sebagai sumber polen. Hasil analisis laboratorium menunjukkan madu hutan hasil panen di KHDTK Rantau memenuhi sebagian kriteria (Standar Nasional Indonesia, 2013) (SNI) 01-3545-2013, terkecuali kadar air. Madu mengandung komponen fitokimia flavonoid, alkoloid, saponin, dan triterpenoid.Kata kunci: Analisis vegetasi, Apis dorsata, kualitas madu, tumbuhan pakan lebah madu